ANALISIS HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN TRANSCRIPT BASED LESSON ANALYSIS (TBLA) PADA PEMBELAJARAN FLUIDA DINAMIS DI SMA - Nurida Ramayanti; Haratua Tiur Maria Silitonga; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study is to analize learning outcomes of student through Transcript Based Lesson Analysis (TBLA) on dynamic fluid in high school at SMA Islam Al Azhar 10 Pontianak. This research method is descriptive qualitative. This study involved 22 students of class XI SMA Islam Al Azhar 10 Pontianak who were taught by a physics teacher who was accustomed to following online Lesson Study. Learning activities were recorded in audio and video, then the recorded data was transcripted in verbal form and analyzed. The results of the transcript analysis are important data to determine the interactions that occur in learning towards student learning outcomes. The results showed that classically, there was a decrease in learning outcomes from cycle 1 to cycle 2, namely the percentage of learning outcomes in cycle 1 was 57,6% and the percentage in cycle 2 was 30,3%. Based on the learning transcript the decline in learning outcomes occurs due to several factors, including a lack of motivation in cycle 2 which causes low student attention and curiosity and learning tends to be boring. Judging from the cognitive abilities of students on the learning outcomes test in cycle 1, the highest average percentage achievement was the cognitive ability to predict (C5) of 90,9%. While the lowest average percentage in cycle 1 is the cognitive ability to analyze (C4) of 36,4%. In cycle 2, the highest average percentage achievement is the cognitive ability to understand (C2) of 45,4%. While the lowest average percentage in cycle 2 is the cognitive ability to apply (C3) of 18,2%. This research is expected to be a guideline and reference in developing learning strategies in physics problems to improve student leatning outcomes.Keyword: Learning Outcomes, Lesson Study, Transcript Based Lesson Analysis (TBLA)